EFFECT OF DENTIN HYBRIDIZATION ON TOOTH STAINING CAUSED BY ROOT CANAL SEALING PASTES FOR PEDIATRIC DENTISTRY (CIPEEX, 2024)
This research project aimed to evaluate dental discoloration caused by root canal sealing pastes used in pediatric dentistry. Blocks of bovine mandibular incisor crowns were prepared. A 2 mm thick enamel and dentin remnant was obtained. The blocks were randomly distributed into two groups according to whether dentin hybridization was performed. After hybridization, the blocks were subdivided into five experimental groups based on the type of endodontic cement: 1) Guedes Pinto Paste; 2) Zinc oxide and eugenol paste; 3) Calcium hydroxide paste, prepared with pure calcium hydroxide and propylene glycol; 4) Paste containing Chloramphenicol + tetracycline chloride + zinc oxide and eugenol; 5) Vitapex®. Color determination was performed using a digital spectrophotometer, with measurements taken 7, 30, and 60 days after material placement. Data on discoloration were tabulated and tested for normality using the Shapiro-Wilk test. ANOVA and Tukey's tests were employed. Root canal paste type and evaluation period showed statistically significant differences in dental color change (p
Keywords: Endodontic cements; tooth discoloration; dentin sealing